2012
DOI: 10.1111/j.1468-2354.2012.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Reference Norms, Staggered Wages, and Wage Leadership: Theoretical Implications and Empirical Evidence*

Abstract: This article presents an extension of the Taylor model with staggered wages in which wage setting is also influenced by reference norms. We show that reference norms can considerably increase the persistence of inflation but that the size of this effect depends on the exact definition (e.g., external vs. internal, symmetric vs. asymmetric norms). Using data on collectively bargained wages in Austria from 1980 to 2006 we show that wage setting is strongly influenced by reference norms, that external norms seem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
5
0
4
Order By: Relevance
“…Second, we do likewise at the industry-by-occupation level, at which collective bargaining agreements between employer associations and unions are typically concluded in Austria, typically distinguishing white and blue collar workers (e.g., white-collar workers in the insurance industry). Most CBAs cover all of Austria; some are state-specific (see Knell and Stiglbauer, 2012). Our industry proxy is 3-digit NACE.…”
Section: External Job Offers and Job Mobilitymentioning
confidence: 99%
“…Second, we do likewise at the industry-by-occupation level, at which collective bargaining agreements between employer associations and unions are typically concluded in Austria, typically distinguishing white and blue collar workers (e.g., white-collar workers in the insurance industry). Most CBAs cover all of Austria; some are state-specific (see Knell and Stiglbauer, 2012). Our industry proxy is 3-digit NACE.…”
Section: External Job Offers and Job Mobilitymentioning
confidence: 99%
“…For Austria, using data on collectively bargained wages, reference norms play a significant role. External norms seem to matter more than internal norms (Knell and Stiglbauer, 2012). However, in an earlier paper, Pollan (2004) found that Austrian remuneration outcomes characterised by high and rising diversity were incompatible with a wage-pattern hypothesis.…”
Section: Literature Reviewmentioning
confidence: 96%
“…homogeneous wage increases). An attempt to systematically study CBA wage floors and wage growth (building on the Statistics Austria-based "CBA wage floor index" (Tariflohnindex) in Knell and Stiglbauer (2012)), was not feasible due to a small number of observations.…”
Section: Firm Wage Premiamentioning
confidence: 99%